Analisis Tingkat Pendidikan dan Tingkat Partisipasi Angkatan Kerja pada Usia Muda terhadap Pengangguran dan Kemiskinan Melalui Upah Minimum Regional di Provinsi Kalimantan Tengah - Thymothy Segah A. R; Alexandra Hukom (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
At the national and regional levels, sustainable strategies are needed to address complex and ongoing issues, including poverty, unemployment, and regional minimum wages. There are two factors that are the focus of this study: Provincial Minimum Wage in Central Kalimantan Province: 1) The Impact of Education Level on Poverty and Unemployment; and 2) The Impact of Early Labor Force Participation Rate on Poverty and Unemployment through the Regional Minimum Wage. Time series data from 2014 to 2023 is used as secondary data in this study. The type of data used is quantitative data. The data was analyzed using path analysis, and SPPS 25 was the analysis tool used. Based on the findings, there is a significant indirect relationship between unemployment and poverty and education level. In addition, there is a significant indirect relationship between unemployment and poverty with the initial labor force participation rate, which is influenced by the regional minimum wage.